Danger on Dartmoor - Lindop, Audrey Erskine 1920-1986; Robertson, Harry 1932-1996 (2021)
"A group of children, lost in fog on Dartmoor, encounter a wild dog, an escaped convict, and other dangers." [imdb.com]
Original: Großbritannien 1980
Keywords: Film; Blu-Ray-Disc